Applying the 7 Ps of Marketing to Enhance Dental Practice Operations and Success - Alessandro Quaranta; Wang Lai Hui (Publymed, 2024)
In the evolving healthcare sector, dental practices face the imperative to adopt robust marketing strategies that attract and retain patients and optimize service delivery and operational efficiency. The 7 Ps of marketing-Product, Price, Place, Promotion, People, Process, and Physical evidence-constitute a comprehensive framework designed to address these multifaceted challenges. This framework not only aims to meet but exceed patient expectations, fostering practice growth and enhancing operational excellence. Each element of the 7 Ps plays a pivotal role in crafting a marketing strategy that is aligned with the core objectives of healthcare marketing and patient care standards. This commentary will analyse the application and the optimisation of the 7Ps framework in dental marketing and operational management.